Trade Credit Insurance - Jones, Peter M. (World Bank, Washington, DC, 2017)
The sales of goods and services are exposed to a significant number of risks, many of which are not within the control of the supplier. The highest of these risks and one that can have a catastrophic impact on the viability of a supplier, is the failure of a buyer to pay for the goods or services it has purchased. In today's challenged domestic and global economic climate, recognizing and managing future risks has become a priority for businesses. Losses attributed to non-payment of a trade debt or bankruptcy can and do occur regularly. Default rates vary by industry and country from year-to-year, and no industry or company is immune from trade credit risk. The essential value of trade credit insurance is that it provides not only peace of mind to the supplier, who can be assured that their trade is protected, but also valuable market intelligence on the financial viability of the supplier's customers, and, in the case of buyers in foreign countries, on any trading risks peculiar to those countries. As well as providing an insurance policy that matches the client's patterns of business, trade credit insurers will establish the level of cover that can reasonably be provided to the supplier for trade with each individual buyer, by analyzing the buyer's financial status, profitability, liquidity, size, sector, payment behavior and location.